1992
DOI: 10.1161/01.cir.86.6.1872
|View full text |Cite
|
Sign up to set email alerts
|

Reentrant and focal mechanisms underlying ventricular tachycardia in the human heart.

Abstract: Both intramural reentry and a focal mechanism underlie sustained VT in patients with healed myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
161
1
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(175 citation statements)
references
References 26 publications
10
161
1
3
Order By: Relevance
“…Reentry circuit isthmuses can be bordered by unexcitable scars that create conduction block. 5,6 Our study shows that VT reentry circuit isthmuses can be identified from delineation of electrically unexcitable scar defined by a high pacing threshold. RF ablation in these regions abolished inducible VT in 10 of 14 patients and abolished or markedly reduced spontaneous VT during follow-up.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Reentry circuit isthmuses can be bordered by unexcitable scars that create conduction block. 5,6 Our study shows that VT reentry circuit isthmuses can be identified from delineation of electrically unexcitable scar defined by a high pacing threshold. RF ablation in these regions abolished inducible VT in 10 of 14 patients and abolished or markedly reduced spontaneous VT during follow-up.…”
Section: Discussionmentioning
confidence: 79%
“…3,4 In human hearts explanted many years after the infarction, extensive fibrosis creating areas of fixed conduction block is often present. 5,6 These observations suggest that reentry circuit isthmuses can potentially be defined during sinus rhythm by delineating the areas of dense, fibrous scar. How best to accomplish this task with catheter mapping has not been established.…”
mentioning
confidence: 99%
“…10,[12][13][14] The abnormal variability in impulse velocity and potential substrate for reentrant circuits may be facilitated in hearts undergoing progressive dilation in which there is dynamic imbalance between distending forces and the stretch-resistant extracellular collagen scaffold during postinfarction LV remodeling. This propensity may be amplified by elevated plasma levels of adrenergic neurohormones after infarction.…”
Section: Discussionmentioning
confidence: 99%
“…6 -8 Although ventricular arrhythmias are common in patients with LV dysfunction and congestive heart failure, 9,10 the relation between LV remodeling and ventricular arrhythmias after acute myocardial infarction has not been explored systematically. 11 Ventricular tachycardia is believed to be due to anisotropic reentry, consequent on slowed impulse propagation velocities through myocardium partially replaced by fibrosis, 10,[12][13][14] which typifies postinfarction remodeling myocardium. In addition, activation of plasma neurohormones after infarction 15 provides a potential electrophysiological substrate for triggering ventricular arrhythmias.…”
mentioning
confidence: 99%
“…15 Myocardial scar-based reentry accounts for only half of the mechanisms of ventricular arrhythmias in patients with nonischemic cardiomyopathy, with the rest having focal initiation of ventricular tachycardia from triggered activity with early afterdepolarizations and delayed afterdepolarizations. 16 Irrespective of the HF cause, patients with advanced HF (stage D) have a different distribution of arrhythmias that may be triggered primarily by pump failure. One series showed that 62% of such patients had severe bradycardia or electromechanical dissociation as the underlying cause for their SCD and only 38% had ventricular tachycardia/ventricular fibrillation.…”
Section: Pathophysiologymentioning
confidence: 99%